Developmental Patterns of Voluntary Pensions in CEE Countries: Analysis through the Bass Diffusion Model Reflecting the Observational Learning Mechanism - Yakymova, Larysa (Bulgarian Academy of Sciences, 2020)
Global population ageing forces governments to transfer pension risks to individuals and employers by introducing voluntary private components into national pension systems. Diffusion theories in combination with behavioural economics can help to understand the nature of developmental patterns of voluntary pensions. This paper modifies the Bass Diffusion Model by introducing hypotheses regarding the information cascade when joining a voluntary pension schemes, a variance of participants' growth and its moderation effect on the information cascade. We trace the diffusion of voluntary pensions in four CEE countries (Bulgaria, the Czech Republic, Romania, and Ukraine), and show that the modified model delivers better overall performance than previous models both in terms of model fit and understanding this process. In addition, we demonstrate that the modified model allows us to correctly describe the wave-like nature of the evolution of voluntary pension provision caused by pension transformations.
Keywords: voluntary pensions; Bass Diffusion Model; observational learning; information cascade; moderation effect; CEE countries